Implementation of Court Decisions that Have Permanent Legal Force by Prosecutors Against Fugitive Convicts on the Wanted List (DPO): A Case Study in Papua, Indonesia - Renjaan, Johanis; Roberth KR Hammar; Carina Budi Siswani (Manunggal Halim Jaya, 2025)
Executing final and binding court decisions is a crucial phase in criminal law enforcement in Indonesia. Particularly in Papua Province, the execution of fugitive convicts on the Wanted List (DPO) faces complex and multidimensional challenges. This study aims to analyze the execution mechanism, identify obstacles faced by prosecutors as decision executioners, and evaluate strategies implemented to improve the effectiveness of executions in Papua. The research method used is normative law with a qualitative approach, which examines secondary legal materials and related empirical data. The research findings show that executions in Papua are not limited to formal legal aspects but are heavily influenced by geographic, socio-cultural, and technological limitations. Rugged terrain, strong customary traditions, and social and community networks that protect fugitives are major obstacles slowing down the enforcement process. Furthermore, administrative issues, such as delays in sending copies of court decisions to the Prosecutor's Office, also hinder executions. These obstacles require a holistic strategy integrating formal law enforcement and cultural approaches. The strategies implemented by prosecutors in Papua include preventive measures, such as cross-institutional supervision and coordination, repressive measures such as formal summonses, the determination of wanted list status, and the forced arrest of uncooperative convicts. This study emphasizes the synergy between legal aspects, information technology, and sensitivity to the local context in addressing these challenges. An adaptive approach considering Papuan sociocultural values has been shown to increase public support and accelerate the execution process. This study recommends strengthening coordination between law enforcement and agencies by developing locally responsive information technology, involving traditional leaders in the legal process, reforming policies, and training law enforcement officials. This will enable more effective, efficient, and equitable implementation of Papua court rulings while strengthening public trust in the criminal justice system.